Preparation and characterization of poly(ethyl hydrazide)-grafted oil palm empty fruit bunch fibre for the removal of Cu(II) ions from an aqueous environment - Johari, Ili Syazana; Yusof, Nor Azah; Haron, Md. Jelas; Mohd Nor, Siti Mariam (Multidisciplinary Digital Publishing Institute, 2013)
Poly(ethyl hydrazide)-grafted oil palm empty fruit bunch fibre (peh-g-opefb) was successfully prepared by heating poly(methyl acrylate)-grafted opefb (pma-g-opefb) at 60 °C for 4 h with a solution of hydrazine hydrate (15% v/v) in ethanol. The Fourier transform infrared spectrum of the product shows a secondary amine peak at 3267 cm-1, with amide carbonyl peaks at 1729 cm-1 and 1643 cm-1. The chelating ability of peh-g-opefb was tested with copper ion in aqueous solution. A batch adsorption study revealed that maximum adsorption of copper ion was achieved at pH 5. An isotherm study showed the adsorption follows a Langmuir model, with a maximum adsorption capacity of 43.48 mg g-1 at 25 °C. A kinetic study showed that the adsorption of copper ion rapidly reaches equilibrium and follows a pseudo-second-order kinetic model, with a constant rate of 7.02 × 10-1 g mg-1 min-1 at 25 °C. The Gibbs free energy, ΔG0, value is negative, indicating a spontaneous sorption process. Entropy, ΔS0, gives a positive value, indicating that the system is becoming increasingly disordered after the adsorption of copper ion. A positive enthalpy value, ΔH0, shows that the endothermic process takes place during the adsorption and is more favourable at high temperatures.